Impacts of COVID-19 on parents with small children in South Korea: survey findings and policy implications. (1st February 2022) - Peng, Ito; Jun, Jiweon
Abstract : The COVID-19 pandemic has emphasised the importance of care and care work, and exposed pre-existing inequalities. Our survey of the impacts of COVID-19 on parents with small children in South Korea reveals that mothers were much more likely to bear the increased burden of childcare than fathers, which, in turn, had direct and negative impacts on their well-being. We discuss how South Korea's dualised labour market, gender-biased employment practice, social norms about childcare and instrumental approach to family and care policies may have contributed to the persistent unequal distribution of unpaid care work within households and gender inequality.